Pharmacokinetics/pharmacodynamics of chloroquine and artemisinin-based combination therapy with primaquine - André Daher; Ghait Aljayyoussi; Dhelio Pereira; Marcus V. G. Lacerda; Márcia A. A. Alexandre; Cristiana T. Nascimento; Júlio Castro Alves; Laís Bastos da Fonseca; Diego Medeiros Dias da Silva; Douglas Pereira Pinto; Danielle Fonseca Rodrigues; Ana Carolina Rios Silvino; et al. (Malaria Journal, 2019)
Abstract Background Activation of hypnozoites of vivax malaria causes multiple clinical relapses, which contribute to the Plasmodium vivax burden and continuing transmission. Artemisinin-based combination therapy (ACT) is effective against blood-stage P. vivax but requires co-administration with primaquine to achieve radical cure. The therapeutic efficacy of primaquine depends on the generation of a therapeutically active metabolite via cytochrome P450 2D6 (CYP2D6). Impaired CYP2D6 metabolism has been associated with primaquine treatment failure. This study investigated the association between impaired CYP2D6 genotypes, drug-exposure to the long-acting ACT component (schizonticidal drugs) and tolerance and efficacy. Methods Adult patients with acute vivax malaria were enrolled in a recently completed trial and treated with artesunate–mefloquine, chloroquine or artemether–lumefantrine. All received concomitant primaquine (0.5 mg/kg/day for 7–9 days). The association between efficacy and safety and drug exposure was explored using area-under-the-curve (AUC) and half-life (t1/2) estimates obtained by non-compartmental analysis of the long half-life drugs. Parasite recurrences by day 63 were categorized as related relapses or re-infections/unrelated hypnozoite activation by genotyping three microsatellite loci and two polymorphic loci of merozoite surface antigen-1. The CYP2D6 genotype was identified with Taqman assays by real-time PCR to 9 polymorphisms (8 SNPs and one deletion). Impaired CYP2D6 activity was inferred using the Activity Score System. Results Most recurrences in the ASMQ (67%), CQ (80%) and AL (85%) groups were considered related relapses. Eight of nine (88.9%) of the patients with impaired CYP2D6 activity relapsed with related parasite compared to 18/25 (72%) with normal activity (RR = 1.23, 0.88; 1.72, p = 0.40). There were no associations between the measured PK parameters and recurrence. Patients with longer chloroquine half-lives had more pruritus (RR = 1.09, 1.03; 1.14, p = 0.001). Higher CQ ...